From Nursing to Courtroom: A Qualitative Descriptive Study of the Preparations, Motivations, and Barriers of Nurses Becoming Lawyers - Estoque, Homelo Valenzuela; Padagas, Reynold Culimay (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: Transitioning is a common phenomenon that happens such as in a career shift provoked by either internal or external factors. This phenomenon also occurs to nurses becoming lawyers. Considering its complexity, such transition entails a process.Purpose: This study aimed to describe and uncover the preparations, motivations, ad barriers of nurses who transitioned into nurse-lawyers in the Philippines. Methods: The study employed descriptive-qualitative research design utilizing twenty participants selected through purposive and snowball or referral sampling techniques. A semi-structured interview guide was used for the data collection using Google form. Braun and Clarkeâ€™s thematic analysis was utilized as the primary treatment of the transcribed data. Strict observance of ethical standards in conducting research was ensured.Results: The study found out several themes and subcategories from the thematic analysis conducted. These included (1) â€œpre-planning emotive expressionsâ€; (2) â€œmotivations of career shiftâ€; (3) â€œsupport mechanisms to afford career shiftâ€; (4) â€œbarriers to career shiftâ€; (5) â€œthe interconnectedness of law and nursingâ€; and (6) â€œimpacts of the career shift.â€ Conclusion: Generally, the career shift of the nurse-lawyers presented significant themes pertinent to their preparations, motivations, and barriers in becoming lawyers. Apparently, these are all primordial in the career transition of the nurse-lawyers. Essentially, the study provides preliminary findings that may become springboard in the construction of a grounded theory that would explicate the transition of the nurse-lawyers as a phenomenon uniting and expanding nursing and the practice of law as complementary sciences.